2010
DOI: 10.1210/jc.2010-0932
|View full text |Cite
|
Sign up to set email alerts
|

Significant Human β-Cell Turnover Is Limited to the First Three Decades of Life as Determined byin VivoThymidine Analog Incorporation and Radiocarbon Dating

Abstract: Under typical circumstances, human β-cells and their cellular precursors are established by young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(182 citation statements)
references
References 14 publications
12
163
0
3
Order By: Relevance
“…Highest rate of beta cell proliferation [21,22] Increased insulin secretion, which is, in part, due to transient insulin resistance [44,45] Doubling of beta cell mass by 5 years of age [22] Several-fold increase in beta cell mass from birth to adulthood [50,51] Increase in beta cells per islet and in islet size [51,52] Evidence of beta cell neogenesis and a regenerative response in diabetes [53] Mature beta cells are sensitive to perturbations in cell cycle control [60] Pro-survival effects of lactogen hormones on beta cells [99,100] but not alpha cells [102] Cytoprotective effect of GLP-1 on beta cells [104] GIP stimulates glucagon secretion [113], while GLP-1 inhibits secretion [112] Increase in beta cell mass reported in obesity [119] Reduction in beta cell mass and relative increase in alpha cell mass in diabetes [74] Decline in beta cell function; decline in beta cell replication Beta cell mass remains relatively constant in healthy humans [121] No major alterations in beta cell size [120] Beta cell apoptosis is low and remains constant throughout life [21] In diabetes: Mitochondrial dysfunction, oxidative stress, ER stress and accumulation of intermediate-sized amyloid particles [127] Neonatal age Puberty Adolescence Adulthood Old age diabetes coupled with high expression of IL-6 receptors on alpha cells suggest that this cytokine could contribute to the increased alpha cell mass observed in diabetes [88]. This notion is supported by fasting hypoglucagonaemia and an inability of mice lacking IL-6 to increase their alpha cell mass.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highest rate of beta cell proliferation [21,22] Increased insulin secretion, which is, in part, due to transient insulin resistance [44,45] Doubling of beta cell mass by 5 years of age [22] Several-fold increase in beta cell mass from birth to adulthood [50,51] Increase in beta cells per islet and in islet size [51,52] Evidence of beta cell neogenesis and a regenerative response in diabetes [53] Mature beta cells are sensitive to perturbations in cell cycle control [60] Pro-survival effects of lactogen hormones on beta cells [99,100] but not alpha cells [102] Cytoprotective effect of GLP-1 on beta cells [104] GIP stimulates glucagon secretion [113], while GLP-1 inhibits secretion [112] Increase in beta cell mass reported in obesity [119] Reduction in beta cell mass and relative increase in alpha cell mass in diabetes [74] Decline in beta cell function; decline in beta cell replication Beta cell mass remains relatively constant in healthy humans [121] No major alterations in beta cell size [120] Beta cell apoptosis is low and remains constant throughout life [21] In diabetes: Mitochondrial dysfunction, oxidative stress, ER stress and accumulation of intermediate-sized amyloid particles [127] Neonatal age Puberty Adolescence Adulthood Old age diabetes coupled with high expression of IL-6 receptors on alpha cells suggest that this cytokine could contribute to the increased alpha cell mass observed in diabetes [88]. This notion is supported by fasting hypoglucagonaemia and an inability of mice lacking IL-6 to increase their alpha cell mass.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%
“…The two groups suggested that human beta cell turnover is limited to the first three decades of life, since no replication (incorporation of IdU) of islet beta cells was detectable in the participants over 30 years of age [121].…”
Section: Old Agementioning
confidence: 99%
“…10 Despite its central importance in metabolic physiology, the β cell in general has a poor capacity to withstand stresses, a feature that is compounded by its limited numbers and low inherent replication rate. 11 From a teleological perspective, the extent to which an individual's β cells adapt to stress may distinguish those insulin resistant individuals who develop diabetes from those who do not. Studying differences in β-cell stress responses in these two populations of individuals ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: β-Cell Dysfunction In Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…However, b-cell proliferation in humans has been reported to rapidly decrease within 5 years after birth, and only minimal b-cell proliferation is observed in adults (6)(7)(8). Estimation of b-cell life span by lipofuscin accumulation or radiocarbon dating has also suggested minimal b-cell turnover in adult humans (9,10). Therefore, clarification of endogenous regenerative capacity in adult humans is critical for interpretation of the results of rodent studies and their application to humans.…”
mentioning
confidence: 99%